2022
DOI: 10.1080/19768354.2022.2099971
|View full text |Cite
|
Sign up to set email alerts
|

Melittin-derived peptides exhibit variations in cytotoxicity and antioxidant, anti-inflammatory and allergenic activities

Abstract: Melittin is a major component of bee venom; it is widely used in traditional medicine because of its therapeutic effects, such as anti-inflammatory effects. However, melittin has limited medical applications owing to its adverse effects, such as high cytotoxicity. In this study, we investigated the physiological activities of various hydrolyzed melittin-derived peptides to eliminate the cytotoxicity of melittin and enhance its efficacy. The 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Interestingly, conjugates can also have the opposite effect when administered at a value less than IC 50 . Moreover, our results are supported by other recent studies, which also suggest that Melittin has antioxidant and anti-inflammatory properties 33 , 34 . On the molecular level, high ROS activity affect cells by attacking molecules such as DNA, proteins, and lipids.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, conjugates can also have the opposite effect when administered at a value less than IC 50 . Moreover, our results are supported by other recent studies, which also suggest that Melittin has antioxidant and anti-inflammatory properties 33 , 34 . On the molecular level, high ROS activity affect cells by attacking molecules such as DNA, proteins, and lipids.…”
Section: Discussionsupporting
confidence: 91%
“…The protein in the acrylamide gel was transferred to the NC membrane using a Mini Trans-Blot Electrophoretic Transfer Cell (Bio-Rad). The blotted membrane was blocked with 5% skim milk in TBST for 1 h. HRP-conjugated goat anti-human IgG Fc cross-adsorbed secondary antibody (1:5000 diluted in TBST containing 5% skim milk) was bound for 1 h. After washing five times with TBST, the experimental results were imaged using ECL (Jung et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that the activation of peripheral P2X and P2Y receptors, transient receptor potential (TRP) vanilloid receptor 1 (TRPV1) and canonical TRP channels might be involved in the pathophysiological processing of MLT-induced hypersensitivity [ 87 , 88 ]. However, the molecular mechanisms by which the innate immune system initiates allergic responses remain largely undiscovered [ 89 ].…”
Section: Toxic Side Effects Of Mltmentioning
confidence: 99%